2016
DOI: 10.1021/acscatal.6b00454
|View full text |Cite
|
Sign up to set email alerts
|

SAD–GLAD Pt–Ni@Ni Nanorods as Highly Active Oxygen Reduction Reaction Electrocatalysts

Abstract: Vertically aligned catalysts comprised of platinum–nickel thin films on nickel nanorods (designated as Pt–Ni@Ni-NR) with varying ratios of Pt to Ni in the thin film were prepared by magnetron sputtering and evaluated for their oxygen reduction reaction (ORR) activity. A glancing angle deposition (GLAD) technique was used to fabricate the Ni nanorods (NRs) and a small angle deposition technique for growth of a thin conformal coating of Pt–Ni on the Ni-NRs. The Pt–Ni@Ni-NR structures were deposited on glassy car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…And after 10,000 cycling tests, the Au@PtNi nanoparticles exhibited a roughly 11.7 mV smaller negative potential shift than Au@Pt nanoparticles (12.7 mV). Various studies have also reported that if PtNi alloy shells are used with other cores such as Pd, Ni, and PtPb, good catalytic activities and stabilities for ORRs can also be obtained [160,388,[559][560][561]. Wang et al [562] also reported that the use of PtCo alloy shells on Pd cores can produce better ORR activities than other samples of Pt/C, Pd/C and Pd@Pt/C, and increased stability in which the maximum power density of Pd@Pt 3 Co/C showed almost no obvious decay in experimental testing.…”
Section: Core-shell-structured Catalysts With Alloy Shellsmentioning
confidence: 99%
“…And after 10,000 cycling tests, the Au@PtNi nanoparticles exhibited a roughly 11.7 mV smaller negative potential shift than Au@Pt nanoparticles (12.7 mV). Various studies have also reported that if PtNi alloy shells are used with other cores such as Pd, Ni, and PtPb, good catalytic activities and stabilities for ORRs can also be obtained [160,388,[559][560][561]. Wang et al [562] also reported that the use of PtCo alloy shells on Pd cores can produce better ORR activities than other samples of Pt/C, Pd/C and Pd@Pt/C, and increased stability in which the maximum power density of Pd@Pt 3 Co/C showed almost no obvious decay in experimental testing.…”
Section: Core-shell-structured Catalysts With Alloy Shellsmentioning
confidence: 99%
“…[45][46][47] Through controlling the roughness factor-that is the ratio of the active surface area to the geometric surface area, promoting single-crystal property, and optimizing FCC orientation, the electrochemical activity of PEM fuel cells can potentially be enhanced. [44][45][46][47][48][49][50][51][52][53] An additional cause for loss in efficiency in operating PEM FCs are cathode catalyst layers. The issue is that utilizing optimally the catalyst material accounts for a large fraction of the overall cost of the fuel cell system.…”
Section: Limitations Of Traditional Pem Fuel Cell Electrodesmentioning
confidence: 99%
“…However, researchers are still working on designing a fuel cell with reduced use of Pt but decreased limitations and issues. [50][51][52]55 The Department of Energy (DOE) is the primary authority that outlines future goals for fuel cell development-especially PEM FCs. The DOE's targets for 2020 are, "14$/kWnet, 5000 hours of durability with cycling, 300 mA/cm 2 performance at 0.8 V, 1000 mW/cm 2 performance at rated power; 20$/m 2 cost, 0.125 mg/cm 2 , g/ kW electrode for [Pt] PEM total loading (both electrodes) less than 40% loss in mass activity.…”
Section: Limitations Of Traditional Pem Fuel Cell Electrodesmentioning
confidence: 99%
See 2 more Smart Citations